2021
DOI: 10.1039/d1ra03251h
|View full text |Cite
|
Sign up to set email alerts
|

Study of deposition parameters and growth kinetics of ZnO deposited by aerosol assisted chemical vapor deposition

Abstract: Impact of deposition parameters, microstructure and growth kinetics analysis of ZnO grown by Aerosol-assisted Chemical Vapor Deposition (AACVD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…32 However, the catalytic system suffered from degradation issues due to morphological changes during CO 2 reduction in aqueous media. ZnO has the distinct advantage of being easily prepared in high quality and in a wide range of nanostructures, such as nanorods, 33,34 nanotubes, 35,36 and nanobelts, 37,38 via solution routes such as chemical bath deposition (CBD)/dip coating, 39 chemical vapor deposition (CVD)/spray pyrolysis, 40 hydrothermal synthesis, 41 and electrochemical deposition. 42,43 Electrodeposition is a low-temperature (mostly <100 °C) cost-effective deposition process that allows the design of complex ZnO nanostructures by combining and adjusting the growth conditions.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 However, the catalytic system suffered from degradation issues due to morphological changes during CO 2 reduction in aqueous media. ZnO has the distinct advantage of being easily prepared in high quality and in a wide range of nanostructures, such as nanorods, 33,34 nanotubes, 35,36 and nanobelts, 37,38 via solution routes such as chemical bath deposition (CBD)/dip coating, 39 chemical vapor deposition (CVD)/spray pyrolysis, 40 hydrothermal synthesis, 41 and electrochemical deposition. 42,43 Electrodeposition is a low-temperature (mostly <100 °C) cost-effective deposition process that allows the design of complex ZnO nanostructures by combining and adjusting the growth conditions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…ZnO has the distinct advantage of being easily prepared in high quality and in a wide range of nanostructures, such as nanorods, , nanotubes, , and nanobelts, , via solution routes such as chemical bath deposition (CBD)/dip coating, chemical vapor deposition (CVD)/spray pyrolysis, hydrothermal synthesis, and electrochemical deposition. , Electrodeposition is a low-temperature (mostly <100 °C) cost-effective deposition process that allows the design of complex ZnO nanostructures by combining and adjusting the growth conditions. ,,, In the late 1990s, Yoshida and co-workers described one-step electrodeposition of nanostructured ZnO/organic films onto conducting substrates for photovoltaic applications, by adding water-soluble dyes such as tetrasulfonated metallophthalocyanines to the electrochemical bath containing Zn­(NO 3 ) 2 . The loading of organic molecules into ZnO films was also attempted using a ZnCl 2 bath employing cathodic reduction of the dissolved molecular oxygen precursor. ,, In the present study, electrodeposited ZnO layers will be used as a matrix for the incorporation of molecular catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon supports the highest deposition rate and thickness in SD films. Due to the very low O 2 concentration in the vacuum chamber, there is minimal reaction between the metal plasma and O 2 , allowing atomic Zn to adsorb on the substrate without reacting with O 2 . This abnormally increases the deposition rate.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the very low O 2 concentration in the vacuum chamber, there is minimal reaction between the metal plasma and O 2 , allowing atomic Zn to adsorb on the substrate without reacting with O 2 . 21 This abnormally increases the deposition rate. The diffraction patterns indicated that the as-deposited films were polycrystalline in nature.…”
Section: Variant O 2 Flow Ratementioning
confidence: 99%
“…Electrodeposition, chemical vapor deposition, magnetron sputtering, hydrothermal, precipitationspin coating and spray pyrolysis methods were utilized to prepare ZnO thin films [7][8][9][10][11]. However, the precipitation-spin coating technique has the merits of being a non vacuum, inexpensive, and simple with low-temperature processing and compositional control.…”
Section: Introductionmentioning
confidence: 99%